2004
DOI: 10.1088/0953-8984/16/39/008
|View full text |Cite
|
Sign up to set email alerts
|

Infrared ellipsometric study on the initial stages of oxide growth on Si(001)

Abstract: The initial stages of native oxide growth on an etched Si(001) surface have been studied by infrared (IR) spectroscopic ellipsometry. The mid-infrared ellipsometric spectra show characteristic vibrational bands of Si-H stretching vibrations between 2100 and 2200 cm −1 , and bands of silicon oxide between 1000 and 1290 cm −1 . The most intense band in the range of Si-H stretching vibrations is assigned to a vibration of SiH 2 groups, while the most prominent bands from the oxide interface can be assigned to ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Additional bands that can not be attributed to nitrobenzene are marked with an asterisk. ides on H/Si(1 1 1) and H/Si(0 0 1) surfaces [20]. The set-up is currently upgraded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional bands that can not be attributed to nitrobenzene are marked with an asterisk. ides on H/Si(1 1 1) and H/Si(0 0 1) surfaces [20]. The set-up is currently upgraded.…”
Section: Discussionmentioning
confidence: 99%
“…The detection limits improved further with the advances in IR technology and most recently it was shown that also ultra thin organic films [19,8] and submonolayers of adsorbates [20] on nonmetallic substrates can be investigated. The instrument presented in this article furthermore allows to achieve this sensitivity for sample areas with diameters of only a few 100 lm.…”
Section: Infrared Ellipsometrymentioning
confidence: 99%
“…So, RAS can be used as a complementary technique to other infrared (IR) spectroscopies (e.g., IR absorption [18,19], IR ellipsometry [20], IR attenuated total reflection [21,22], Raman scattering [23,24], and sumfrequency generation [25,26]), which have a prominent bulk signal that might obstruct the detection of surface phonons. The far-infrared reflectance anisotropy spectroscopy (FIR-RAS), being an optical technique, does not damage the sample and can be applied to investigate surfaces of samples embedded not only in vacuum, but also in a gas or a liquid.…”
Section: à2mentioning
confidence: 99%
“…Hydrogenated Si(111) surfaces have a low rate of surface charge carrier recombination, which means that this surface is well-passivated [8]. However, this surface is not stable and oxidizes rapidly in contact with ambient air [9]. For this reason, a way to avoid this degradation is to form covalent Si-C bonds which can be obtained by various methods initiated chemically [10], electrochemically [11,12], thermally [13] or photochemically [14].…”
mentioning
confidence: 99%